THE EFFECTIVENESS OF TEAM ASSISTED INDIVIDUALIZATION TYPE AND NUMBERED HEAD TOGETHER TYPE OF COOPERATIVE LEARNING MODEL TOWARD STUDENTS LEARNING OUTCOMES IN STUDENTS CLASS X OF TECHNIQUES VEHICLES LIGHT OF SMK MUHAMMADIYAH MLATI SLEMAN - Winda Deskaprina; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2017)
The use of less precise learning model makes students less understand with the material explained by teachers and cause to low learning outcome in mathematics. This study aims to determine which is more effective between cooperative learning model of TAI and NHT on the results of students' mathematics learning. The population in this study were students of grade X techniques vehicles light (TVL) of SMK Muhammadiyah Mlati Sleman in academic year of 2015/2016. Technique sampling using random sample of the class and the grade XA TVL as the class that uses cooperative learning type of TAI, and grade XB TVL as a class using type of cooperative learning of NHT. Data collection technique is to use the test. The research instrument is the mathematics result test in the form of an objective questions. Instruments test include validity, distinguishing capacity and reliability testing. Analysis of the data used is the prerequisite test analysis consists of a normality test and homogeneity test. Then the hypothesis test using t-test two sides and one side. Based on the calculation ofÂ t-test in two sides in this research with a significant level of Î± = 5% and degrees of freedom df = 48, then obtained which means that there are differences in learning mathematics result between students learning using cooperative learning model type of TAI with students whose learning using cooperative learning model type of NHT. And based on the calculation of t-test in one side with significance level Î± = 5% and degrees of freedom df = 48, then obtained which means that the learning mathematics using cooperative learning model of TAI type is more effective than using NHT type on the students' mathematics learning outcome in class X TVL of SMK Muhammadiyah Mlati Sleman in the Academic Year of 2015/2016.